Developing a Culturally Integrated E-Module on Madurese Herbal Knowledge to Enhance Students’ Ecoliteracy Skills - Junaedy, Andri Gunawan; Handayani, Rif’ati Dina; Asyiah, Iis Nur (Lectura : Jurnal Pendidikan, 2025)
The lack of learning media makes the learning process monotonous and boring, and the lack of introduction to local wisdom makes students less familiar with the surrounding culture. E-modules can be a solution to convey material on elements, compounds, and mixtures that are integrated with Madurese herbal medicine. The aim of this research is to design, validate, and evaluate the effectiveness of an integrated e-module that combines science learning materials with Madurese herbal medicine local wisdom to enhance students’ ecoliteracy. The method used in this study was research and development with four stages, namely, define, design, develop, and disseminate. Data collection techniques included observation techniques, interviews, and questionnaires. The results of this study, at the validation stage, showed there were four aspects that were assessed, namely content feasibility, which obtained a value of 90%; presentation aspect, 86.67%; linguistic aspect, 94.47%; and graphic feasibility, 93.33%. The total percentage obtained was 91.12%, which means that the developed e-module is valid and feasible to use. Meanwhile, the results of ecoliteracy skills in the cognitive aspect obtained an N-gain of 0.5 and were included in the moderate category. Other results in the attitude aspect obtained 92.39%, and the results of the skills aspect obtained 93.12%, so that they were classified as very effective. In conclusion, integrating local wisdom into science learning through a well-designed e-module not only strengthens students’ understanding of scientific concepts but also fosters cultural appreciation and environmental responsibility, thereby supporting the development of ecoliterate future generations.